Penerapan TQM Untuk Pengendalian Kualitas Pada Proses Penenunan Di Tenun Bantarjo - Yunitasari, Elly Wuryaningtyas; Wijaya, Fikri Singgih (DHARMA BAKTI, 2021)
Quality control is a crucial issue in the weaving process at Bantarjo Weaving. Therefore, in 2019 at Bantarjo RT 17 RW 09, Banguncipto, Sentolo, Kulon Progo, community service was conducted by becoming a speaker at the Bantarjo weaving group with the theme Application TQM for quality control in the weaving process in Bantarjo weaving. We find the cause of weaving defects and reduce weaving defects; quality control efforts need to be analysed. The percentage of weaving defects becomes small using the Fishbone method and the Total Quality Management (TQM) approach. Supervision is carried out on each process of weaving woven fabrics to obtain quality woven fabric products. The Bantarjo Weaving Group controls the quality of all matters relating to the production process, from the raw materials used from preparing raw materials such as yarn and dyes to the operation of unification of woven fabrics. The method that can be used to overcome product defects is to identify the work process flow of woven fabric. The Fishbone Diagram method is one of the methods/tools in improving quality. This diagram is also often called a cause-and-effect diagram. Of all the processes of making woven fabrics, it is necessary to control and continuously improve if there are product defects. Defective products are used to make other products, so they are not wasted. From the Industrial Engineering Study Program team, we, Universitas Sarjanawiyata Tamansiswa Yogyakarta, made the Bantarjo weaving group as our mentor.